Changes to household food shopping practices during the COVID-19 restrictions: Evidence from the East of England. (November 2022) - Thompson, Claire; Hamilton, Laura; Dickinson, Angela; Fallaize, Rosalind; Mathie, Elspeth; Rogers, Samantha; Wills, Wendy
Abstract: Measures to control the spread of COVID-19 have changed the way we shop for food and interact with food environments. This qualitative study explored food shopping practices in the East of England, a large diverse region including coastal, urban and rural settings. In 2020/2021 we interviewed 38 people living in the region and 27 professionals and volunteers providing local support around dietary health. Participants reported disruption to supermarket shopping routines; moving to online shopping; and increased reliance on local stores. COVID-19 has impacted disproportionately upon lower-income households and neighbourhoods. The longer-term implications for dietary health inequalities must be investigated. Highlights: Measures to control the spread of COVID-19 have change the way we shop for food. Reduced frequency of shopping trips and increased pre-planning was widely reported. Those on low incomes and without access to a car faced greater challenges. The shift to 'local' shopping may have amplified dietary health inequalities.